A study Some Physico-Chemical And Bacterial Properties of Wastewater for Ramadi Teaching Hospital and its Impact on the Euphrates River - Ali Ibrahim Edan1 , Mohammed Muslih Sharqi2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Physiochemical and bacteriological characteristics of Euphrates river water were examined monthly to assessthe possible impacts of wastewater discharged from Ramadi Teaching hospital for the period from August2019 to January 2020. The obtained results showed that air and water temperature mean values varied from12.0 ±11.3 to 40.0 ± 11.3 C ° and from9.1.0 ±3.12 to 33 ±9.5 C° respectively. Also, turbidity values werefound to range from 14.0±8 to 144 ±9.6 NTU. while EC value was situated between 567.0±44.67 ?S/cmand2899 .0±274 .3?S/cm. The current results have shown that total hardness mean values were very highand ranged between 252.0±27.5 and1114.0±96.3 mg/l while chlorides mean values ranging from92.0±62to 588 ±104 mg/l, but nitrate mean values were found with the range of 1.2 ±1.86 and 50 ±4.5mg/l.TheBOD mean values were found to range from1.0 ±1.2 to 34 ±6.5 mg/l, while DO mean values varying from1.7 ±3 to 11.1 ±1.3 . This study has shown that the total bacterial count (222 to 1800000 cells/1 ml), TotalColiform (61 -170000 cells/100 ml), Fecal Coliform (0-58000 cell/100 ml), and Fecal Streptococci (18-9200 cells/100 ml).